2014
DOI: 10.1164/rccm.201408-1452oc
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of DNA Methylation and Gene Expression in Idiopathic Pulmonary Fibrosis

Abstract: Rationale: Idiopathic pulmonary fibrosis (IPF) is an untreatable and often fatal lung disease that is increasing in prevalence and is caused by complex interactions between genetic and environmental factors. Epigenetic mechanisms control gene expression and are likely to regulate the IPF transcriptome.Objectives: To identify methylation marks that modify gene expression in IPF lung. Methods:We assessed DNA methylation (comprehensive highthroughput arrays for relative methylation arrays [CHARM]) and gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 60 publications
6
126
1
Order By: Relevance
“…Epigenetic changes that are associated with age (33,34) seem to be highly conserved in mammals (35,36), especially the global change of DNA methylation patterns, also known as the "epigenetic clock." This particular loss of methylation and the subtle differences between changes in healthy aging and in age-related pathological processes (37) could be the key to identifying novel biomarkers in IPF, since it exhibits its own particular methylation profile (38).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
“…Epigenetic changes that are associated with age (33,34) seem to be highly conserved in mammals (35,36), especially the global change of DNA methylation patterns, also known as the "epigenetic clock." This particular loss of methylation and the subtle differences between changes in healthy aging and in age-related pathological processes (37) could be the key to identifying novel biomarkers in IPF, since it exhibits its own particular methylation profile (38).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
“…We intersected the 2,130 IPF-associated DMRs with recently identified loci from the two published genome-wide association studies in IPF [49,50] and identified methylation changes in genes within 5 of these loci [113]. Of special interest are genes that are differentially expressed in IPF lung and whose expression may be regulated by both genetic variants and DNA methylation.…”
Section: Methylation Changes Within the Ipf Genetic Locimentioning
confidence: 99%
“…Although many changes in the epigenome have unknown function, we are beginning to elucidate those associated with IPF. A recent study by Yang et al identified over 2,000 differentially methylated regions (DMRs) of which almost half were associated with changes in gene expression [113].…”
Section: Chapter III Dna Methylation Of the Muc5b Promoter In Ipf Intmentioning
confidence: 99%
“…In the latest report, Yang, et al, using comprehensive high-throughput arrays for relative methylation methodology, examined 4.6 million CpG sites distributed across the human genome, and simultaneously, the gene expression changes in lung tissues from 94 IPF patients and 67 control subjects 29 . They found that the IPF lungs have a large number of disease-associated methylation changes that also affect gene expression in the opposite direction.…”
Section: Dna Methylationmentioning
confidence: 99%
“…After birth, many of these pathways are suppressed or restricted to tissue-specific stem cell maintenance, but may be re-expressed in response to tissue injury in a strictly regulated pattern favoring tissue regeneration, or deregulated contributing to adult diseases, including IPF. Thus, the analyses of transcriptional and epigenetic signatures have revealed that IPF lungs are significantly enriched with genes and networks associated with lung development, mainly WNT/β-catenin and sonic hedgehog (SHH) signaling pathways 29,40 . In IPF lungs, the WNT/β-catenin signaling pathway with its main canonical signal transducers, Gsk-3β and β-catenin, has been detected to be significantly activated mainly in hyperplastic type II epithelial cells, with nuclear translocation of β-catenin and over-expression of its response genes, like cyclin D1 and matrix metalloprotease-7 41,42 .…”
Section: Putative Sequence Of the Cellular And Molecular Pathogenic Mmentioning
confidence: 99%